Before the coffee gets cold - Kawaguchi, Toshikazu, 1971-; Trousselot, Geoffrey (London : Picador, an imprint of Pan Macmillan, 2019)
In a small back alley in Tokyo at a century-old coffee shop rumored to offer patrons the chance to travel back in time, four customers reevaluate their formative life choices.
In a small back alley of Tokyo, there is a café that has been serving carefully brewed coffee for more than one hundred years. Local legend says that this shop offers coffee-- and the chance to travel back in time. Over the course of one summer, four customers visit the café in the hopes of making that journey. There are rules that must be followed. And the most important one: the trip can last only as long as it takes for the coffee to get cold. -- adapted from jacket
The lovers -- Husband and wife -- The sisters -- Mother and child.
"Originally published in Japanese in 2015 as Coffee Ga Samenai Uchimi by Sunmark Publishing, Inc., Tokyo, Japan."--Title page verso.
First published.
Donated by Farhana Zahir, Assistant Professor, BRAC Business School
In English. Translated from the Japanese.
Keywords: Coffeehouses -- Japan -- Tokyo -- Fiction; Time travel -- Fiction; Interpersonal relations -- Fiction; Voyages dans le temps -- Romans, nouvelles, etc; Japanese fiction; Fictional Work